Virtual Laboratory and Numeracy Ability in Basic Physics Practicum: A Literature Review - Febby Apriani; Almira Erika Putri; Rindi Sartika Dwi Oktari; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2024)
The rapid development of technology has significantly impacted various sectors, particularly the field of education. One of the learning innovations widely used in basic physics practicum is the virtual laboratory. Virtual laboratories enable students to conduct interactive experiments that improve conceptual understanding and numeracy skills through simulations that help them understand physics concepts while also improving numeracy ability in analyzing data, performing calculations, and interpreting experimental results. This study aims to analyze the role of virtual laboratories in improving numeracy ability in basic physics practicum through a literature review approach. This research uses a qualitative method with a literature review design. The data sources were obtained from scientific articles indexed in Google Scholar with a publication range from 2015–June 2024.